PENGARUH STRATEGI PEMASARAN PRODUK PENDANAAN TERHADAP JUMLAH NASABAH PT. BANK SYARI’AH MANDIRI KCP BENGKALIS - Nur Azlina (STAIN Bengkalis, 2020)
The marketing strategy is basically a whole plan, integrated and unified field of marketing, which provides guidance on activities to be carried out in order to achieve the marketing objectives of a company. Marketing strategy standalone Islamic bank KCP Bengkalis, to encourage customers to participate in activities such as banking, namely, location, promotion, and product sharing. Marketing is human activity directed to meet and satisfy the needs and human desires through the exchange process. Establishment of site selection Islamic Bank Mandiri KCP Bengkalis positively to the value of 6.589 on the variable increase the number of customers using 4 indicators, strategies, location, location and comfort. With four variables used in this study proved that the location variable has the highest influence. In this research, using a sampling method with random sampling technique. Then the retrieval of data by using a questionnaire containing open and closed questions. From the data obtained was then processed using statistical linear regression formula with the help of software SPSS 16. From the results obtained, the location variables have the most influence and significant to the variable increase in the number of customers of Bank Syariah Mandiri KCP Bengkalis. Keyword: Marketing Strategies, Increasing Number of Customers